Pengaruh Komite Audit, Komisaris Independen, Kepemilikan Institusional terhadap Nilai Perusahaan dengan Profitabilitas sebagai Moderating pada Bank yang Terdaftar di Bursa Efek Indonesia (Tahun 2017-2023) - Yuanna Hanova Ayu; Bambang Satriawan; Robin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the impact of the audit committee, independent commissioners, and institutional ownership on firm value, with profitability as a moderating variable, for banks listed on the Indonesia Stock Exchange (IDX) from 2017 to 2023. The background of this research highlights the importance of good corporate governance in enhancing firm value, particularly in the banking sector, which plays a crucial role in the economy. The study seeks to analyze the extent to which these corporate governance factors influence firm value and the role of profitability in moderating these effects. This research employs a quantitative method with purposive sampling, collecting data from 48 banks listed on the IDX, of which only 15 met the sample criteria. The results show that the audit committee has a significant impact on firm value, with a t-statistic of -2.028192 and a probability of 0.0453. Conversely, independent commissioners and institutional ownership do not have a significant impact on firm value. Additionally, profitability does not significantly modify the relationship between the audit committee and firm value but has a significant effect on moderating the relationship between independent commissioners and firm value. Profitability does not influence the modification of the relationship between institutional ownership and firm value.